The Difference in Serum Levels of IP-10 in Pulmonary Tuberculosis Patients with Positive AFB and AFB Conversion - Said Muchsin; Herry Priyanto; Teuku Zulfikar; Ferry Dwi Kurniawan; Novita Andayani; Budi Yanti (Jurnal Respirologi Indonesia, 2022)
Background: Tuberculosis (TB) is caused by Mycobacterium tuberculosis, which most commonly infects the lungs. Diagnostic modalities are required in smear-negative TB. IP-10 is a potent chemokine for detecting the presence of TB infection. This study aimed to determine the difference in serum IP-10 levels in patients with smear-positive pulmonary TB and pulmonary TB patients with AFB conversion after two months of therapy.Methods: This was an analytic observational study with a cross-sectional approach. Sampling was carried out by consecutive sampling methods. AFB examination was performed using Ziehl-Neelsen staining, and serum IP-10 was measured using ELISA.Results: The study results obtained mean IP-10 levels in TB patients with smear positive and AFB conversion after two months of treatment of 459 pg/mL and 204.4 pg/mL, respectively. Statistical analysis using independent t-test received P<0.0001. The optimal cut-off value was 306,1 pg/ml (90% sensitivity; 95% specificity; area under the curve: 0.948, 95% CI=0.88-1; P=0.0001). Conclusion: There was a significant difference between IP-10 levels in TB patients with smear positive and AFB conversion